Raoultella Bacteremia Presenting as an Acute Self-Limited Illness in an Obstetric Patient - Justin Choi; Iqra Sheikh; Melissa Carr; Robert Shapiro; Karen Fluet (Hindawi Limited, 2020)
A 20 year-old female at 27-week gestation was admitted for threatened preterm delivery. Following an initially unremarkable hospital course for 12 days, the patient developed fever, chills, generalized malaise, abdominal pain, and diffuse myalgias on day 13 of hospitalization. Raoultella species was isolated from blood cultures on day 16 of hospitalization. The patient's condition improved within 24 hours of symptom onset, prior to antibiotic initiation, and a premature, viable male infant at 29 weeks and 6 days of gestation was delivered via caesarean section four days later due to breech presentation in the setting of preterm labor. Here, we present the first case of a Raoultella species infection in a gravid female reported in the literature.